Proposals for the improvement of the school organization of the Cuban primary school - Laguna Cruz, Jorge Alejandro (Avances en Supervisión Educativa, 2010)
The organization of the school penetrates all of the activities that the family and community have total success at the school with the pupils, the workpeople, the teachers in the making. Planning rationally the regimen of day of a school, he requires integrating different processes whereon the institution audits student with the aim of achieving the objectives of Model of school. In this work the authors propose how making the activities of in-fashion regimen at the elementary school  perfect Cuban. The authors lean on the validation of experiences of the Escuela Provincial for directors of Education Primary Holguín's, Cuba. Aftermath respond to the fulfillment of fact-finding running Project.